Comparison of Biventricular Function between Pregnant and Non-Pregnant Women by Conventional and Newer Echocardiographic Indices - Razak, Abdul; Priyanka, Antony; Padmakumar, R.; Nayak, Krishnananda (International Journal of Cardiovascular Practice, 2018)
Introduction: Pregnancy is a physiological process associated with increased cardiac output, blood volume, decreased systemic vascular resistance and other metabolic changes. The purpose of this study was to evaluate biventricular function between pregnant and non-pregnant women by conventional and newer echocardiographic indices.Methods: Echocardiography was done at the beginning of the second and third trimester for 51 (18-24 GW) pregnant women and age-matched 50 non-pregnant women were included in this study. Patients were assesses based on their sex, age, detailed history, and anthropometric values. Moreover, cardiac investigations including echocardiography and tissue Doppler imaging were performed.Results: The mean age of pregnant women was 27 Â± 3, and the non-pregnant woman was 24 Â± 4 years. When compared with control during pregnancy left ventricular (LV) end-diastolic volume was increased, and LV ejection fraction was decreased for women in second to third trimester. Right ventricular (RV) function increased significantly (P < 0.05) in the third trimester when compared with control. RV tissue Doppler early diastolic filling wave Eâ gradually decreased during pregnancy.Conclusions: During pregnancy, left ventricular ejection fraction & contractility is reduced. The myocardial peak velocity changes occurred throughout pregnancy. Echocardiographic indices of ventricular function were used to detect the changes in cardiac function during both normal and high-risk pregnancy.